AKIBAT HUKUM TERHADAP PEMBELI BERITIKAD TIDAK BAIK DALAM TRANSAKSI JUAL BELI TANAH - Yoliandri Nur Sharky; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2021)
This research explains how the criteria of buyers are not good and the legal consequences of buyers have bad intentions in buying and selling land in the case of the 1943K / Pdt / 2019 verdict. The research method used is a normative juridical research method. The data source used is secondary data. Data collection techniques use literature study techniques. The results showed that: 1) land buyers were declared badly intentioned buyers in the case of 1943K / Pdt / 2019 because buying and selling was done not using a legal rights basis because they did not research and be careful in buying and selling land that caused buying and selling contrary to the law, namely unfulfilled Article 1320 of the Civil Code, material requirements and formal conditions of land buying and selling, and did not meet the criteria of buyers with bad intentions according to SEMA No.4/2016. 2) The legal consequences of the buyer in bad faith cause the agreement to buy and sell land until the issuance of the certificate of land rights becomes null and void and has no binding legal force. Conclusion of this study 1) The criteria of buyers with bad intentions is that buyers are not careful and do not research the land purchased, buying and selling using unauthorized rights, rejecting the good faith of the seller, not meeting the requirements of Article 1320KUH Civil, do not meet the material requirements and formal requirements of buying and selling land, and do not meet the criteria of buyers in good faith SEMA No.4/2016.